Resistance training among competitive mountain bikers and adherence to recommended training guidelines - Mitchell, S. M.; Higginbotham, J. C.; Richardson, M. T.; Wingo, J. E.; Henderson Mitchell, R. J.; Usdan, S. L. (The Sport Journal, 2018)
The sport of mountain biking provides an ideal avenue for examining sport specific training. Research has identified mainstays in mountain bike performance, which include peak power output (PPO) and mean power output (MPO). Resistance Training (RT) has been shown to increase muscular strength. An increase in strength can increase power output (PO). Increases in power would allow an athlete to perform at higher given workloads. A stronger individual will typically produce greater sustained PO, thereby increasing sport performance. The purposes of this study were to identify the prevalence of RT among competitive mountain bikers, as well as to determine if riders are adhering to the recommended guidelines shown to increase sport performance. Forty competitive mountain bikers responded to a nationwide online training survey assessing exercise training. Fifty-five percent of respondents reported participating in RT during the in-season. Mean number of workout sessions per week devoted to RT was 3.0 ± 1.2 days per week. Fifty-two and a half percent of respondents reported participating in RT during the off-season. Mean number of workout sessions per week devoted to RT was 2.8 ± 1.1 days per week. No significant difference (t = 0.8, df = 15, p = 0.4) in the number of workout sessions per week between seasons was shown. Results suggest that riders are adhering to the recommended resistance training guidelines associated with increases in sport performance. To increase performance, competitive mountain bikers should consider implementing RT into his or her workout regimen.